Exploring EFL Students’ Perceptions of Google Classroom as Learning Management System - Madar Aleksius; Floribertha Lake; Elisabet Andriyanti Werang; Maria Febriani Seran (Universitas Hamzanwadi, 2022)
The employment of Information Technology (IT) for the online teaching and learning process is unavoidable nowadays. One of the popular online teaching platforms currently used in ELT is Google Classroom. However, the literature indicates that there is a limited number of research investigating the perceived usefulness and effectiveness of Google Classroom viewed by the students as its end-users. Thus, the current study aims at investigating the perceptions of secondary students in using Google Classroom (GC) as a Learning Management System (LMS) in English Language Teaching (ELT0. The study focuses on three variables: perceived usefulness (PU), perceived ease of use (PEOU), and actual system use (AU). The study employed a mixed-method research design for data collection and analysis. Quantitative data was collected using a questionnaire and analyzed using IBM SPSS 25.0. The qualitative data was obtained through in-depth interviews with nine respondents. The findings suggest that most participants have positive views on GC with some reservations. Students seem to have more expectations before using GC; yet, they experienced dissatisfaction afterward. It was revealed that GC provides various features to support English learning, but it depends on the users to maximize them. It is suggested that more digital technology training and workshops for students and teachers be adequately fluent in using the GC. Schools need to establish policies to enforce the use of GC within schools, conduct preparation for teachers and students, provide technical support, and collaborate with other institutions for capacity building.